Humanities, culture, and interdisciplinarity : the changing American academy - Klein, Julie Thompson (State University of New York Press, 2005)
"The study of culture in the American academy is not confined to a single field, but is a broad-based set of interests located within and across disciplines. This book investigates the relationship among three major ideas in the American academy - interdisciplinarity, humanities, and culture - and traces the convergence of these ideas from the colonial college to new scholarly developments in the latter half of the the twentieth century. Its aim is twofold: to define the changing relationship of these three ideas and, in the course of doing so, to extend present thinking about the concept of "American cultural studies." The book includes two sets of case studies - the first on the implications of interdisciplinarity for literary studies, art history, and music; the second on the shifting trajectories of American studies, African American studies, and women's studies - and concludes by asking what impact new scholarly practices have had on humanities education, particularly on the undergraduate curriculum."--Jacket